2023
DOI: 10.1038/s43247-023-00910-6
|View full text |Cite
|
Sign up to set email alerts
|

Approaching a thermal tipping point in the Eurasian boreal forest at its southern margin

Mukund Palat Rao,
Nicole K. Davi,
Troy S. Magney
et al.

Abstract: Climate change is increasing the intensity and frequency of extreme heat events. Ecological responses to extreme heat will depend on vegetation physiology and thermal tolerance. Here we report that Larix sibirica, a foundation species across boreal Eurasia, is vulnerable to extreme heat at its southern range margin due to its low thermal tolerance (Tcrit of photosynthesis: ~ 37–48 °C). Projections from CMIP6 Earth System Models (ESMs) suggest that leaf temperatures might exceed the 25th percentile of Larix sib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…In the cold region, increased average temperature was the dominant climatic factor of the declined trend in ecosystem resilience (Figure 5). The niche of ecosystems in cold regions is narrow, and the suitable temperature range is limited (Lancaster, 2022; Rao et al., 2023). A previous study showed that the temperature change ranges tolerated by ecosystems in cold regions are 1 K lower than those of temperate ecosystems (Heyder et al., 2011), meaning that the increased average temperature likely exceeds the safe temperature boundary of ecosystems in cold regions.…”
Section: Discussionmentioning
confidence: 99%
“…In the cold region, increased average temperature was the dominant climatic factor of the declined trend in ecosystem resilience (Figure 5). The niche of ecosystems in cold regions is narrow, and the suitable temperature range is limited (Lancaster, 2022; Rao et al., 2023). A previous study showed that the temperature change ranges tolerated by ecosystems in cold regions are 1 K lower than those of temperate ecosystems (Heyder et al., 2011), meaning that the increased average temperature likely exceeds the safe temperature boundary of ecosystems in cold regions.…”
Section: Discussionmentioning
confidence: 99%
“…Photosystems I and II are protein complexes that play central roles in photosynthetic light reactions and are particularly sensitive to temperature (Havaux, 1993). Photosynthetic heat tolerance is often quantified as the critical temperature above which photosystem II (PSII) sustains irreversible damage based on minimal chlorophyll a fluorescence experiments ( T crit (°C); Schreiber & Berry, 1977, O'Sullivan et al ., 2017, Rao et al ., 2023). Due to their potential influence on fitness in hotter environments, these critical limits are of interest for understanding species' fundamental niches (Aspinwall et al ., 2019; Feeley et al ., 2020) and sensitivity to extreme events such as heatwaves (Andrew et al ., 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Forests 2024, 15, 50 2 of 13 was documented, as well as a general increase in gross and net primary productivity within the Siberian forests and forest-tundra zones [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%